Nano-film coated cathode functional layers towards high performance solid oxide fuel cells. Issue 25 (6th June 2018) - Choi, Mingi; Lee, Jongseo; Lee, Wonyoung
Abstract : Nano-structured composite electrodes, from a carefully conducted infiltration process, are one of the most promising electrode structures for intermediate temperature solid oxide fuel cells (IT-SOFCs), due to their ability to promote the oxygen reduction reaction (ORR) and enlarge triple phase boundaries (TPBs). Abstract : Nano-structured composite electrodes, from a carefully conducted infiltration process, are one of the most promising electrode structures for intermediate temperature solid oxide fuel cells (IT-SOFCs), due to their ability to promote the oxygen reduction reaction (ORR) and enlarge triple phase boundaries (TPBs). Here, we demonstrate rational design of infiltrated nano-structures for IT-SOFCs with enhanced ORR kinetics and excellent stability. We systematically designed a nano-structured cathode functional layer (CFL) from the infiltration of Sm0.5 Sr0.5 CoO3− δ (SSC) into porous Gd0.2 Ce0.8 O2− δ (GDC). By controlling the drying process during the infiltration process, two distinct nano-structures of SSC, discrete coating and film-like coating, were fabricated on the GDC scaffolds. The CFL with the film-like coating showed ∼30% reduction in polarization resistance ( R p ) and ∼15% increase in peak power density at 650 °C compared to the CFL with the discrete coating in spite of ∼12-fold lower loading of infiltration materials. Furthermore, the CFL with the film-like coating showed an excellent stability, maintaining an R p of 0.029 Ω cm 2 for 100 h at 650 °C. Our results demonstrated that the high performance and stability of composite electrodes for IT-SOFCs can be achieved through a thin-film coated CFL.